1996
DOI: 10.1007/bf00335704
|View full text |Cite
|
Sign up to set email alerts
|

Systemic liberation of interleukin-1? and interleukin-1 receptor antagonist in the perioperative phase of liver transplantation

Abstract: We measured systemic serum levels of interleukin-1 receptor antagonist (IL-1ra), interleukin-1 beta (IL-1 beta), tumor necrosis factor alpha (TNF-alpha), and interleukin-6 (IL-6) during the preoperative, anhepatic, and postreperfusional phases up to the 7th postoperative day in 60 patients undergoing orthotopic liver transplantation (LTx). In contrast to IL-1 beta, IL-1ra, TNF-alpha, and IL-6 showed a significant elevation in relation to the early phase after reperfusion, while TNF-alpha displayed a high grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
1
Order By: Relevance
“…30 Another explanation for this finding might be that peak IL-1␤ levels were related to duration of cold ischemia time and IL-1␤ levels in donor plasma, in contrast to other cytokines. A previous study 31 also showed greater IL-1␤ levels after long cold ischemia times, but in contrast to that report, we found a significant increase in IL-1␤ concentrations in all our patients.…”
Section: Discussioncontrasting
confidence: 99%
“…30 Another explanation for this finding might be that peak IL-1␤ levels were related to duration of cold ischemia time and IL-1␤ levels in donor plasma, in contrast to other cytokines. A previous study 31 also showed greater IL-1␤ levels after long cold ischemia times, but in contrast to that report, we found a significant increase in IL-1␤ concentrations in all our patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In response to injury, trauma, or infection, cytokines play an important role in the acute phase. The proinflammatory cytokines IL-1, IL-6, and TNFa participate in a synergetic manner to mediate inflammation in this acute phase response [3].…”
Section: Introductionmentioning
confidence: 99%